2018
DOI: 10.1016/j.ccr.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic catalysis in biological media and living settings

Abstract: Organometallic catalysis has allowed the development of an impressive number of chemical transforma-28 tions that could not be achieved using classical methodologies. Most of these reactions have been accom-29 plished in organic solvents, and in many cases in the absence of water, and under air-free conditions. The 30 increasing pressure to develop more sustainable transformations has stimulated the discovery of metal-31 catalyzed reactions that can take place in water. A particularly attractive extension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 133 publications
0
77
0
Order By: Relevance
“…These processes, to date mostlyc leavage or cross-coupling reactions, use abiotic substratesa nd metal-based catalysts and can occur with remarkable efficiency and bioorthogonal selectivity. [5,6,10] Catalysts are administered at low concentrations, thus moderating metal toxicityconcerns.…”
Section: Transition-metal-mediated Bioorthogonal Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…These processes, to date mostlyc leavage or cross-coupling reactions, use abiotic substratesa nd metal-based catalysts and can occur with remarkable efficiency and bioorthogonal selectivity. [5,6,10] Catalysts are administered at low concentrations, thus moderating metal toxicityconcerns.…”
Section: Transition-metal-mediated Bioorthogonal Catalysismentioning
confidence: 99%
“…An umber of recent review articles revise the achievements of catalytic metallodrugs and metal-based bioorthogonal catalysis. [1,[5][6][7][8][9][10][11] In this Concept article, we insteada im at picking out key examples and concepts that have laid the foundations for the use of catalysis in medicinal inorganic chemistrya nd relate them to recent discoveries obtained in our laboratory.T ot his end, we put our focuso nh ow innovative catalystd esign hypotheses have openedt on ew chemistries for application in therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐induced self‐assembling processes, such as metal complexion,, metallogelation,, and so on, can be considered as a special kind of metal‐mediated reactions. Recently, De Cola and Biedermann et al .…”
Section: Reaction‐based Aie‐active Fluorescent Probes: Metal‐mediatedmentioning
confidence: 99%
“…While transition metals are often associated with the well-known toxicity of anticancer drugs such as cis-platins, an umber of publications have demonstrated that there is an interesting windowo fo pportunity. [5][6][7] While the term bioorthogonal chemistry was initially coined for ligationr eactions, bond cleavage reactions are also of interesti nc hemicalb iology to uncage substrates, inhibitors or af unctionalg roup of interest. [8] Light is an attractive external stimulant to trigger such cleavagee vents since it can be controlled both in time andspace.Not surprisingly,photolabile groups to unmaskt he functiono famolecule with spatiotemporal control have been extensively used in chemical biology.…”
Section: Introductionmentioning
confidence: 99%